2018
DOI: 10.1002/lary.27401
|View full text |Cite
|
Sign up to set email alerts
|

Activity of swallowing‐related neurons in the medulla in the perfused brainstem preparation in rats

Abstract: Objectives/Hypothesis We aimed to investigate and validate the cellular activity patterns and the potential topographical organization of neurons of the medullary swallowing pattern generator (Sw‐CPG). We used the perfused brainstem preparation as an innovative experimental model that allows for stable neuronal recording in the brainstem. Study Design Animal model. Methods Experiments were conducted in 14 juvenile Wistar rats. The activities of the phrenic, vagus, and hypoglossal nerves were recorded at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
(147 reference statements)
1
19
0
Order By: Relevance
“…The results of previous studies have shown that the majority of the interneurons controlling the pharyngeal stage of swallowing are orthodromically activated by either the SLN or glossopharyngeal nerve, suggesting that sensory signals (produced by the bolus transit through the pharyngeal cavity) may modulate the sw‐CPG to aid an efficient food bolus transfer into the esophagus. We speculate that swallowing interneurons that were excited by concomitant SLN‐stimulation indeed could be mainly associated with the sensory feedback regulation of pharyngeal swallow rather than pre‐determined sequential output signals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of previous studies have shown that the majority of the interneurons controlling the pharyngeal stage of swallowing are orthodromically activated by either the SLN or glossopharyngeal nerve, suggesting that sensory signals (produced by the bolus transit through the pharyngeal cavity) may modulate the sw‐CPG to aid an efficient food bolus transfer into the esophagus. We speculate that swallowing interneurons that were excited by concomitant SLN‐stimulation indeed could be mainly associated with the sensory feedback regulation of pharyngeal swallow rather than pre‐determined sequential output signals.…”
Section: Discussionmentioning
confidence: 99%
“…The nerve signals were integrated with a 1‐ms time constant and full‐wave rectified. The detailed surgical and recording procedures were described in a recent study to perform recordings from the swallowing‐related neurons in the dorsal medulla . All other basic experimental procedures of perfused brainstem preparation were in accordance with previous reports …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations